Uslub - Rumadani Sagala (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Uslub is a linguistic style used in Arabic language for making the sentences delivered sound and refined; and in so doing those who study Arabic should pay serious attention to Shorof (phonetics), Nahwu (syntacs) and Balaghah (stylistics) where Uslub is an integral part of it. The main objective of studying Uslub is eventually for understanding al-Quran. Uslub contains of three: scientific, khitabi, and literary genre: Ma’ani, Bayan, and Badi’.